E-Ciencias de la Información: An electronic journal serving the transfer of knowledge - Sandí, Magda Cecilia (2011)
The article introduces the concept of E-Science and its importance in the generation of knowledge. In view of this, the School of Library and Information Sciences of the University of Costa Rica could turn to media such as the electronic magazine E-Science of Information. It explains why the modality of electronic publication was chosen and describes the development strategy, design architecture and technological requirements. The article concludes that electronic publications have penetrated strongly in the academic world and are increasingly cited, so their contribution as vehicles for the dissemination of knowledge is undeniable.